2015
DOI: 10.12693/aphyspola.128.128
|View full text |Cite
|
Sign up to set email alerts
|

IR and Raman Investigation of Some Poly(acrylic) Acid Gels in Aqueous and Neutralized State

Abstract: The modication of local polymeric conformation of poly(acrylic) acid (PAA), induced by hydration and neutralization with triethanol amine (TEA), was investigated by IR and Raman spectroscopy. The eect of water is the perturbation of hydrogen bonds established between dierent polymeric chains and the modication of the local conformation of the polymer. The neutralization with TEA aects the carboxylic groups and modies the local conformation of the polymer. These modications are correlated with the shift and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 20 publications
4
51
0
Order By: Relevance
“…Based on the position of Raman lines, it is concluded that the amount of adsorbed water is low (typically below 10 wt %). Furthermore, the local dynamics of PAA nanofiber/microfiber affecting the molecular polarizability was investigated in this work and is confirmed by previous studies . It is worthwhile to mention here that water has its own Raman lines.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Based on the position of Raman lines, it is concluded that the amount of adsorbed water is low (typically below 10 wt %). Furthermore, the local dynamics of PAA nanofiber/microfiber affecting the molecular polarizability was investigated in this work and is confirmed by previous studies . It is worthwhile to mention here that water has its own Raman lines.…”
Section: Resultssupporting
confidence: 85%
“…Technically, this makes almost impossible to use the Raman spectrometer to measure a water droplet, as the reflected laser beam is very weak and hence, the noise masks the absorption lines (however, the spectrum is nicely recorded in the transmission configuration). Consequently, the analysis was focused on the shift of some Raman lines due to the water retention within the nanofibers, which is in agreement with results reported in the literature . This approach is not very sensitive to the presence of water and hence, relatively small amounts of water adsorbed by the polymer will not be reflected in the Raman spectrum but will be observed during TGA experiments.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations